DIFTERI PADA ANAK: FAKTOR-FAKTOR YANG MEMPENGARUHI KEMATIAN - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1989)
Diphtheria is still one of the endemic diseases in Yogyakarta and the mortality rate remains high. There were 94 cases admited to the Dr. Sardjito Hospital during period April 1982-December 1983 and the case fatality rate was 20.2%. Mortality was influenced by clinical manifestation, immunization status nutrition, institution of treatment and occurence of the complications